2019
DOI: 10.4102/koedoe.v61i1.1531
|View full text |Cite
|
Sign up to set email alerts
|

A checklist of the termites of Kruger National Park, South Africa

Abstract: The protection of biodiversity is critical to ecosystem function and is a primary management goal for conservation areas globally. Maintaining a current inventory of known diversity is a central component of achieving this goal and serves as an essential starting point for future research endeavours. Since the first published survey of termites in South Africa’s Kruger National Park (KNP) over 55 years ago, our understanding of termite diversity has expanded sufficiently to merit an update and formal checklist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Most of the prey detected in the guts could not be identified to species level because of a lack of reference sequences for South African invertebrates, a number of undescribed species present, and also the difficulty discriminating between related termite species (Uys, 2002; Lind & Davies, 2019). The unidentified sequences might also represent erroneous reads, particularly when they were represented by a low number of copies (Coissac et al ., 2012), and therefore we did not include those rare prey into the final dataset.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the prey detected in the guts could not be identified to species level because of a lack of reference sequences for South African invertebrates, a number of undescribed species present, and also the difficulty discriminating between related termite species (Uys, 2002; Lind & Davies, 2019). The unidentified sequences might also represent erroneous reads, particularly when they were represented by a low number of copies (Coissac et al ., 2012), and therefore we did not include those rare prey into the final dataset.…”
Section: Discussionmentioning
confidence: 99%
“…Termite genera known to build mounds in Kruger comprise of Macrotermes , Odontotermes and Trinervitermes (Lind & Davies, 2019). Odontotermes and Trinervitermes build mounds that are mostly too small to be recorded using LiDAR data, and Trinervitermes are comparatively rare in Kruger (Davies et al, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…Termite genera known to build mounds in Kruger comprise of Macrotermes, Odontotermes and Trinervitermes (Lind & Davies, 2019).…”
Section: Study Sites and Experimental Designmentioning
confidence: 99%
“…First, as an index of prey availability, we used a metric based on mean annual precipitation. Termite species and likely ants are influenced by rainfall (Davies et al, 2014; Lind & Davies, 2019). Although we did not make species‐specific predictions, Davies et al, (2015) sampled termites in KNP and Hluhluwe‐Imfolozi and observed that termite species diversity, frequency of termite activity and intensity of termite activity all were highest at sites with intermediate (~550 mm) annual precipitation; this was true for sampling in dry, wet and transitional seasons alike.…”
Section: Methodsmentioning
confidence: 99%
“…Ant and termite distributions are influenced primarily by rainfall, geology (soil type), degree of inundation and interactions with vegetation (e.g. Dalerum et al, 2019; Davies et al, 2014; Lind & Davies, 2019). For instance, mound‐building Macrotermes in Kruger National Park (hereafter, KNP) are associated with woody vegetation, granitic soils, areas of lower rainfall and higher elevations (Davies et al, 2014), while mound‐building Odontotermes prefer undulating topography and granitic soils (Meyer et al, 1999).…”
Section: Introductionmentioning
confidence: 99%